Assessment of protein synthesis rate enables metabolic profiling of resident-immune cells of the islets of Langerhans - de Brito Monteiro, Lauar; Archambault, Anne-Sophie; Soukhatcheva, Galina; Dai, Derek; Velghe, Jane; Chen, Yi-Chun; Verchere, C. Bruce; Klein Geltink, Ramon I. (Frontiers in Immunology, 2025)
Pancreatic islet-resident immune cells, such as lymphocytes and macrophages, support islet homeostasis, beta cell development, and tissue repair. In pathological states, including diabetes, islet immune cells can trigger inflammation, causing beta cell dysfunction and death. There has been growing interest in understanding the dynamics between beta cells and resident immune cells. Studying metabolic adaptations in beta cells and immune cells is challenging due to the mixed cell populations in islets and limited cell number, which are not suitable for conventional approaches, such as metabolomics and extracellular flux analysis. We implemented a puromycin-based flow cytometry assay for parallel analysis of the phenotype and metabolic state of islet-resident immune cells. Islets were isolated from healthy mice and exposed to a cytokine cocktail (IL-1β, TNF-α, IFN-γ) to mimic a pro-inflammatory diabetogenic microenvironment. We found that Islet-resident macrophages show higher expression of CD86 and lower expression of CD301 upon cytokine treatment, which was accompanied by reduced protein synthesis rates upon inhibition of glycolysis and mitochondrial complex V. In insulin-producing beta cells, inhibition of mitochondrial complex V (ATP synthase) by oligomycin reduces translation rates. Streptozotocin (STZ)-induced beta cell death promoted accumulation of macrophages in the islet and higher frequency of CD86+ macrophages, as was observed in vitro. Islet macrophages from STZ-treated mice showed higher basal protein synthesis rates and enhanced sensitivity to oligomycin. We validated this method in bone marrow-derived macrophages and the MIN6 beta cell line, using extracellular flux analysis as a control for the puromycin-based assay. We propose our implementation of a puromycin-based assay as a useful tool to study metabolic demands in rare islet cell populations. Applying phenotypic and protein synthesis assays coupled with specific metabolic pathway inhibitors to intact pancreatic islets can provide a better understanding of the immunometabolic cues that lead to beta cell dysfunction and failure in diabetes.